Family Aggression Screening Tool (FAST): Factor structure and psychometric properties of subscales. (May 2022) - Vieira, Renata; Pires, Pedro Paulo; Cecil, Charlotte; Barker, Edward; Reis, Daniela; Couto, Isabella; Cypriano, Cybele; de Oliveira, Irismar Reis
Abstract: Background: The Family Aggression Screening Tool (FAST) is an instrument to screen for experiences of maltreatment using primarily pictorial representations, including direct victimisation and exposure to intimate partner violence. The initial psychometric properties of the FAST were reported in the original research in the United Kingdom. Objective: This research aimed to replicate and to extend the evaluation of the psychometric properties of FAST in Brazil. Participants and setting: Data consisted of 648 youth aged 11 to 17 years from public schools in Brazil. Method: We employed confirmatory factor analysis (CFA), exploratory factor analysis (EFA) and exploratory graphical analysis (EGA). Concurrent validity was supported by strong correlations between the FAST's emotional and physical victimisation subscales and Childhood Trauma Questionnaire (CTQ) emotional and physical abuse subscales. Results: CFA resulted in a solution including second and first order factors, resembling the original structure. FAST's reliability was assessed both through internal consistency and test-retest, showing favorable coefficients. Conclusion: Our results suggest that FAST has good psychometric properties for the Brazilian population with respect to both its validity and reliability.